Unraveling Causes and Consequences of International Retirement Migration to Coastal and Rural Areas in Mediterranean Europe - Gianluca Egidi; Giovanni Quaranta; Luca Salvati; Filippo Gambella; Enrico Maria Mosconi; Antonio Giménez Morera; Andrea Colantoni (Land, 2020)
In a context of aging, low fertility, and progressive slowdown of both internal population mobility and international migration at working age, residential mobility at older ages was regarded as an emerging phenomenon in Mediterranean Europe, a region with increasingly attractive retirement places. The present work discusses the socioeconomic processes (and the environmental impacts) associated with an increasing flow of retirees, which decide to settle from ‘Northern’ countries to Southern Europe, concentrating in coastal districts and in rural countryside. Understanding lifestyle preferences and territorial patterns of residential mobility at older ages allows a refined analysis of short- and medium-term impacts of International Retirement Migration (IRM) on population dynamics in economically growing and declining regions. A refined analysis reveals that destinations of IRM are progressively enlarging from strictly coastal places to a broader set of locations in the rural countryside. Mobility choices among retirees may jeopardize the role of spatial planning, which is increasingly asked to provide specific services for an international, elder population, e.g., stimulating re-use of abandoned rural buildings. Taken as an effective option for rural development, an improved planning and management of local districts attracting and hosting intense flows of residential mobility at older ages is urgent in the present socioeconomic context. A convenient set of policies and a refined taxation system may contribute to reconcile demographic shrinkage with local competitiveness and social cohesion.